2020
DOI: 10.1038/s41559-020-01336-5
|View full text |Cite
|
Sign up to set email alerts
|

Geological alteration of Precambrian steroids mimics early animal signatures

Abstract: The absence of unambiguous animal body fossils in rocks older than the late Ediacaran has rendered fossil lipids the most promising tracers of early organismic complexity. Yet much debate surrounds the various potential biological sources of putative metazoan steroids found in Precambrian rocks. Here we show that 26methylated steranes-hydrocarbon structures currently attributed to the earliest animals-can form via geological alteration of common algal sterols, which carries important implications for paleo-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…If they were validated the molecular record of sponges would be more than 100 Ma prior to the earliest record of siliceous spicules (Antcliffe et al 2014). However, sponge origin of the supposed biomarkers has been challenged by a number of studies (e.g., Antcliffe 2013;Botting and Muir 2018;Botting and Nettersheim 2018;Nettersheim et al 2019;Bobrovskiy et al 2020;van Maldegem et al 2020;Love and Zumberge 2021). In addition, coprostane was proposed as a metazoan biomarker and detected in the iconic Ediacaran fossil Dickinsonia (Bobrovskiy et al 2018).…”
Section: Chemofossilsmentioning
confidence: 99%
“…If they were validated the molecular record of sponges would be more than 100 Ma prior to the earliest record of siliceous spicules (Antcliffe et al 2014). However, sponge origin of the supposed biomarkers has been challenged by a number of studies (e.g., Antcliffe 2013;Botting and Muir 2018;Botting and Nettersheim 2018;Nettersheim et al 2019;Bobrovskiy et al 2020;van Maldegem et al 2020;Love and Zumberge 2021). In addition, coprostane was proposed as a metazoan biomarker and detected in the iconic Ediacaran fossil Dickinsonia (Bobrovskiy et al 2018).…”
Section: Chemofossilsmentioning
confidence: 99%
“…This assumption is corroborated by molecular estimates (Dohrmann & Wörheide, 2017;dos Reis et al, 2015), the presence of a putative sponge fossil from 890 Ma (Turner, 2021) and diagnostic of pre-Marinoan (<650-635 Ma) demosponges (Love et al, 2009;Love & Summons, 2015), and possible cryostane demosponges biomarkers indigenous to bitumens and oils compatible with pre-Sturtian metazoans (<800-740 Ma) (Brocks et al, 2016). However, new evidence calls into question the veracity of biomarkers from the first metazoans, drawing attention to the fact that they may be algal biomarkers, which are common during the Neoproterozoic (Bobrovskiy et al, 2021;van Maldegem et al, 2021).…”
Section: Emergence Of Metazoan Hemocyaninsmentioning
confidence: 99%
“…Trace amounts of 24-ipc and 26-mes have also been reported in hydrogenated lipid extracts from Rhizaria (31), although attempts to replicate these results have not been successful (23). Subsequent studies demonstrated 24-ipc and 26-mes form abiotically from certain C 29 sterols during laboratory pyrolysis under conditions that may mimic diagenesis (26, 32). These studies suggest that the previously observed Rhizarian 24-isopropyl and 26-methyl steranes may have been generated through laboratory pyrolysis rather than by in vivo synthesis and that Neoproterozoic 24-ipc and 26-mes may have formed abiotically from algal sterols.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of 24-ipc and 26-mes as biomarkers for demosponges has been controversial and continues to be debated for several reasons (19)(20)(21)(22)(23)(24)(25)(26). For example, 24-isopropyl sterols have been identified in pelagophyte algae which produce the structurally related compound 24-n-propylcholesterol as their major sterol (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%